(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdcdGe aj GdOdI GdYbdjI hGdTQYjI GdeegOI dGSJfHGW GdCMcGe GdTQYjI , bO JbOe aj Chd eHGMK GdCdaGX JYQja Yde GdCUhd hCfg Yde HGdbhGYO GdJj cHQi GdGSJfHGW hGdaQV ef chfgG cHQis
(3BNQgG (B:s
(3BNQgG(B: (3MJi Efg bjd dg Cf jHYV ajbQC aj Jdc GdaQjVI GdhGMOI LgQG hGNaGJG aQGLY GdcJH GdabgjI aj gPg GdeSCdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs